Handbook of herbs and spices - Peter, K. V. (Cambridge : Woodhead ; Boca Raton, FL : CRC Press, 2001)
Together with its companion volumes, Volume 2 provides a comprehensive and authoritative coverage of key herbs and spices. Chapters on individual plants cover such issues as description and classification, production, chemical structure and properties, potential health benefits, uses in food processing and quality issues
Includes bibliographical references and index
Keywords: Food industry and trade -- Quality control; Herbs; Spices